(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The relevance of the topic of this article is due to the great importance in the national musical culture of the work of the outstanding representative of the song tradition Zhetysu – Kenen Azerbayev, whose 140th anniversary the country will celebrate next year. The peculiarities of the geographical location of the south-west of Zhetysu and a number of historical factors are prerequisites for intercultural interaction, namely, the commonality of a number of features in the songs of the Kyrgyz and K.Azerbayev. The purpose of the article is to consider the Kazakh-Kyrgyz relations in the work of K.Azerbayev. The tasks include: a brief description of the interaction of the above-mentioned cultures in the Kazakh-Kyrgyz border area and consideration of the main features characteristic of the songs of the Kyrgyz and K.Azerbayev. A systematic approach, as well as structural and comparative-typological research methods were applied in the work. The results of the study can be used in further musical and Turkic studies, as well as as additional material in the curriculum of the discipline “Music of the Turkic peoples”.